THE ROLE OF SWOT ANALYSIS TO IDENTIFY INTERNAL FACTORS AND EXTERNAL IN THE STUDENT ACTIVITY UNIT (UKM) LASKAR BIMA CRAFT (LBC) STIT SUNAN GIRI BIMA - Mariani Mariani; Helmi Haris (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to explore the influence of internal and external factors on the Laskar Bima Craft (LBC) Student Activity Unit (UKM) at STIT Sunan Giri Bima by using SWOT analysis techniques (Strengths, Weaknesses, Opportunities, Threats). The method used in this study is qualitative with a case study approach, aiming to provide an in-depth picture of the state of the organization. Data collection was carried out through interviews, observations, and documentation involving members, consumer LBC management. The findings of this study show that the main strength of LBC lies in its function as a forum for student skill development and entrepreneurship, innovation in local products, and has a lot of products such as sofas, batik, and many more as well as support from university institutions. However, there are weaknesses seen in the limited human resources, communication between members in the organization, and the approach to digital marketing that is still lacking. Significant opportunities arise due to the increasing interest by kansumen and students in local handicraft products and also cooperation between SMEs, while the threat comes from competition between SMEs and declining interest in members. By utilizing SWOT analysis, obtaining development strategies that can increase competitiveness between SMEs, strengthen product character, and maximize the entrepreneurial potential of students in the campus environment.